METHODICAL-APPARATUS PROBLEMS OF MONITORING GEOPHYSICAL RESEARCHES AND WAYS OF ITS SOLUTION (ON EXAMPLE OF GEOPHYSICAL SEISMOPROGNOSTIC MONITORING IN TRANSCARPATHIANS) - NAZAREVYCH, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
In the article on example of geophysical seismoprognostic monitoring researches in Transcarpathians the ways of solution of number of problems of methodical-apparatus supplying of such researches are considered.